(3JMUjd GdebUhO ajeG WdH ef JYQja UjZ GdYbhOs - (3eMeO Hf YHO Gddg Hf CMeO HGShOGf,J (B1281 (3g` s ((3YeQ Hf CMeO GdLjdGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde hHYO abO WdH efi GdSjO eMeO Hf MSjf Hf LYaQ Hf eMeO GdYWGS HGYdhi Cf CcJH dg cjaj cJGHI UjZ GdeYGedGJ s
(3BNQgG (B:s
(3hCeG UjZI GdeSJhdOI aMjfFmP UGQJ Hg Ce hdO jMQe HjYgG hJYJb HYO ehJg ef QCS GdeGd hHGddg GdJhajb Je s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3Gdabg GdTGaYjs